Constitutional Challenges of Digital Bureaucracy: Efficiency and Sovereignty in the Disruption Era - Amusroh, Mohammad Rizal; Ichlas, Rudy Iskandar; Jufri, Nur Nashriany (As-Siyasi: Journal of Constitutional Law, 2025)
The digital transformation of bureaucracy has become a strategic agenda for efficient, transparent, and accountable governance. In Indonesia, this transformation was institutionalized through Presidential Regulation No. 95 of 2018 on the Electronic-Based Government System (SPBE). However, digital governance should not be seen merely as a technocratic project. From a constitutional law perspective, digitalization must adhere to the principles of the rule of law, human rights protection, and national sovereignty. This transformation also promotes innovation and strengthens public participation in monitoring and criticizing government policies, thus enhancing democracy. This article critically examines the implementation of digital bureaucracy within the constitutional law framework. The analysis focuses on whether digitalization improves government efficiency or creates challenges related to digital sovereignty, legal accountability, and equal access. Using normative legal research methods, the study analyzes primary sources, such as legislation, alongside secondary sources, including legal doctrine and academic works on constitutional law and digital governance. The findings show that digital bureaucracy can significantly improve public service quality. However, without a strong legal and constitutional framework, digitalization risks being merely an efficiency myth. Indonesia’s reliance on foreign digital infrastructure threatens digital sovereignty and may undermine constitutional guarantees. Therefore, the development of digital bureaucracy should be seen not only as administrative modernization but also as a constitutional mandate, balancing efficiency with constitutional principles, ensuring inclusivity, equal access, and strengthening digital sovereignty through a robust legal foundation and effective oversight